I, journalist and other newsroom introspections - Salud, Joel Pablo (Quezon City, Philippines : UP Press, 2020)
Just plain compelling compelling storytelling, then, from the light bulb advertorial as literal and figurative career moment, to the almost inhuman standards that most journalists hold themselves up against.
I, Journalist -- Conversation between Two Cats -- The Objectification of Objectivity -- My letter to the youth -- Journalists at war -- That place of Honor -- Mentorship -- Ethics, Petiks, Atbp. -- Sleepless in Dutsland -- Thinking and the journalist -- Llosa and the writer as Rebel -- The Journalist and the Executioners -- The Hypocritic Oath -- State of the Nation-State -- For Whom the Bell Trolls.
Keywords: PHILIPPINE ESSAYS (ENGLISH)